Experience of the patriotic education of university students based on ethno-cultural traditions of the Kazakh People - MUSAKHANOVA, G; KALYBEKOVA, A; TORYBAYEVA, A; AITZHANOVA, A; BULETOVA, L (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe article sets out the experimental work that was aimed at modeling and experimental testing of the identified conditions in the educational process of training future. Also, the authors present the results of testing the system of the organization of the patriotic education of students based on the ethno-cultural traditions of the Kazakh people. The experimental data presented by the authors confirmed the effectiveness of the organization of the patriotic education of university students based on the ethno-cultural traditions of the Kazakh people in the process of teaching a foreign language. RESUMENEl artículo expone el trabajo experimental que tuvo como objetivo el modelado y las pruebas experimentales de las condiciones identificadas en el proceso educativo del futuro entrenamiento. Además, los autores presentan los resultados de las pruebas del sistema de organización de la educación patriótica de los estudiantes basada en las tradiciones etno-culturales del pueblo Kazajo. Los datos experimentales presentados por los autores confirmaron la efectividad de la organización de la educación patriótica de estudiantes universitarios basada en las tradiciones etno-culturales del pueblo Kazajo en el proceso de enseñanza de una lengua extranjera.